On the Photochemistry of 1, 2‐Benzisoxazole: Capture of Elusive Spiro‐2H‐azirine and Ketenimine Intermediates. Issue 24 (25th July 2016) - Nunes, Cláudio M.; Pinto, Sandra M. V.; Reva, Igor; Fausto, Rui
Abstract : The photochemistry of 1, 2‐benzisoxazole (1 ) was studied using low‐temperature matrix isolation coupled with infrared spectroscopy and quantum chemistry calculations. We identified, for the first time, spiro‐2 H ‐azirine2 and ketenimine3 as intermediates in the photoisomerization of1 to 2‐cyanophenol (4 ). These results constitute indirect evidence for the existence of vinylnitrene intermediates in the photochemistry of 1, 2‐benzisoxazoles. The potential energy surface (PES) resulting from the N–O bond cleavage of1 was compared with the respective PES of the parent isoxazole. Calculations at the CBS‐QB3 level show that no stabilization is gained for the triplet vinylnitrene upon introduction of a benzene ring fused with isoxazole. However, the energies of2 and3 are higher by 13–15 kcal/mol comparing with the 2 H ‐azirine and ketenimine analogs resulting from isoxazole, which explains why they had not been observed before. Our general mechanistic proposal also predicts well the photoisomerizations of2 and3 to4 . Abstract : We have identified, for the first time, spiro‐2 H ‐azirine and ketenimine as intermediates in the photoisomerization of 1, 2‐benzisoxazole to 2‐cyanophenol. These results constitute indirect evidence for the existence of vinylnitrene intermediates in the photochemistry of 1, 2‐benzisoxazoles.